Seventeen‐year study shows rise in parapneumonic effusion and empyema with higher treatment failure after chest tube drainage. (11th November 2013) - Yu, Danny; Buchvald, Frederik; Brandt, Bodil; Nielsen, Kim G
Abstract Aim To evaluate epidemiology, pre‐admission characteristics and management of paediatric parapneumonic effusions (PPEs) and empyema in a tertiary paediatric pulmonary centre between 1993 and 2010. Methods Retrospective chart review study using paediatric and thoracic database searches, with particular emphasis on pre‐admission characteristics, disease stage (simple or complex effusion or empyema), general management and surgical procedures. Results One hundred children were eligible, exhibiting a significant increase in incidence from 0.5 to 2.6 per 100 000 across the study period. Baseline characteristics were similar across disease stages. Streptococcus pneumoniae was the most common pathogen. Surgical intervention beyond chest tube drainage (CTD) was required in 50%; this rate showed a particular increase in children aged 0–5 years (OR, 3.1), but was otherwise not influenced by baseline characteristics, disease stage or use of intrapleural fibrinolytics. Length of hospitalisation did not differ across disease stages or primary interventional procedures. Conclusion This study confirmed an increasing incidence of PPEs and empyema in a Scandinavian tertiary paediatric pulmonary centre. Young children exhibited higher treatment failure after CTD. Length of hospitalisation was similar across disease stages and was comparable to previous reports according to primary interventional procedure.